A masing event in NGC 6334I: contemporaneous flaring of hydroxyl, methanol, and water masers. Issue 1 (26th April 2018) - MacLeod, G C; Smits, D P; Goedhart, S; Hunter, T R; Brogan, C L; Chibueze, J O; van den Heever, S P; Thesner, C J; Banda, P J; Paulsen, J D
ABSTRACT: As a product of the maser monitoring program with the 26 m telescope of the Hartebeesthoek Radio Astronomy Observatory (HartRAO), we present an unprecedented, contemporaneous flaring event of 10 maser transitions in hydroxyl, methanol, and water that began in 2015 January in the massive star-forming region NGC 6334I in the velocity range −10 to −2 km s −1 . The 6.7 GHz methanol and 22.2 GHz water masers began flaring within 22 d of each other, while the 12.2 GHz methanol and 1665 MHz hydroxyl masers flared 80 and 113 d later, respectively. The 1665 MHz, 6.7 GHz, and 22.2 GHz masers have all remained in their flared state for nearly 3 yr. The brightest flaring components increased by factors of 66, 21, 26, and 20 in the 12.2 and 6.7 GHz methanol, 1665 MHz hydroxyl, and 22.2 GHz water maser transitions, respectively; some weaker components increased by up to a factor of 145. We also report new maser emission in the 1720, 6031, and 6035 MHz OH lines and the 23.1 GHz methanol line, along with the detection of only the fifth 4660 MHz OH maser. We note the correlation of this event with the extraordinary (sub)millimetre continuum outburst from the massive protostellar system NGC 6334I-MM1 and discuss the implications of the observed time lags between different maser velocity components on the nature of the outburst. Finally, we identify two earlier epoch maser flaring events likely associated with this object, which suggest a recurring accretive phenomenon that generates powerful radiative outbursts.